THE MEASUREMENT OF HIGHER-ORDER THINKING SKILLS: A SYSTEMATIC LITERATURE REVIEW - Nia Kania; Yaya Sukjaya Kusumah (Malaysian journal of learning & instruction, 2025)
Purpose - This article comprehensively examines the existing body of literature about the assessment tools employed for evaluating higher-order thinking skills (HOTS) in mathematics within the last five years. The study endeavors to offer a comprehensive overview of measuring instruments for HOTS in mathematics, utilizing precise and up-to-date global data. Methodology - The research adheres to the PRISMA methodology, employing the systematic literature review (SLR) technique, encompassing ten distinct steps. By utilising the Scopus database, this review comprehensively analyses 18 scholarly articles written in English. Findings - The results emphasize the significance of implementing a thorough evaluation approach that integrates standardized exams alongside other assessment methods to measure students' cognitive capacities in advanced mathematical reasoning precisely. The tendencies that have been observed provide valuable insights for the development of evaluation tools that can effectively measure effectiveness in many academic domains. Educators can augment instructional efficacy and foster heightened levels of cognitive reasoning in students by comprehending the equilibrium between evaluative and non-evaluative elements, while recognizing the significance of Bloom's taxonomy. Furthermore, this research presents opportunities for additional investigation, enabling scholars to delve into novel approaches and metrics, thus contributing to breakthroughs in education and improving student proficiencies in critical thinking and problem-solving. Significance – This research provides the opportunity to enhance our comprehension of incorporating higher-order thinking skills in education, thereby promoting holistic cognitive growth.